Does physical activity during pregnancy adversely influence markers of the metabolic syndrome in adult offspring? A prospective study over two decades. Issue 8 (16th May 2013) - Danielsen, Inge; Granström, Charlotta; Rytter, Dorte; Hammer Bech, Bodil; Brink Henriksen, Tine; Vaag, Allan Arthur; Olsen, Sjurdur Frodi
Abstract : Background: It is unknown whether physical activity during pregnancy (PA) has long-term impact on the metabolic profile of the offspring. We investigated associations of PA with markers of the metabolic syndrome (MS) in 20y old offspring. Methods: Longitudinal study where 965 pregnant women during 1988–1989 had four dimensions of PA assessed by questionnaires in gestation week 30: PA at work; leisure time PA, daily amount of walking-biking and sport participation. The following MS markers were assessed in the offspring (n=439): body mass index (BMI), waist circumference, blood pressure, homeostasis model assessment insulin resistance as well as fasting plasma glucose, triglycerides, cholesterol (high-density lipoprotein (HDL), low-density lipoprotein and total cholesterol), insulin and leptin levels. Results: Walking-biking PA in pregnancy is associated with unchanged or subtle, adverse changes of distinct MS markers among offspring including lower levels of HDL cholesterol (ratio 0.95 (95% CI 0.92 to 0.98) per 1 h increment in walking-biking), a higher diastolic blood pressure (difference 1.12 (95% CI 0.03 to 2.20) mm Hg/1 h increment) and a higher BMI (ratio 1.03 (95% CI 1.01 to 1.05) per 1 h increment). In separate analyses in males, these associations persisted and additional adverse associations were found for triglycerides, systolic blood pressure, waist circumference and leptin. No associations were detected with other measures of PA. Conclusions: The study did not substantiate any protective effects of PA in pregnancy. In contrast, data suggested that high amounts of daily walking-biking in pregnancy may have adverse effects on levels of HDL cholesterol, diastolic blood pressure and BMI in young adult offspring.